2018
DOI: 10.29262/ram.v65i1.293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de sensibilización y alergia al kiwi (Actinidia deliciosa) en adultos con enfermedades alérgicas

Abstract: The prevalence of sensitization to kiwi fruit is not a rare event; in contrast, symptoms related to its consumption are uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Они могут проявляться как в виде локального дискомфорта (сыпь или накожное раздражение от контакта с соком), так и более системно -ринит, конъюнктивит и даже анафилактический шок. [25] Поэтому, если ранее вы никогда не пробовали киви или фреш из него, начинайте знакомство с напитком осторожно, с небольших доз, чтобы убедиться в отсутствии аллергической реакции.…”
Section: предупреждает развитие остеопорозаunclassified
“…Они могут проявляться как в виде локального дискомфорта (сыпь или накожное раздражение от контакта с соком), так и более системно -ринит, конъюнктивит и даже анафилактический шок. [25] Поэтому, если ранее вы никогда не пробовали киви или фреш из него, начинайте знакомство с напитком осторожно, с небольших доз, чтобы убедиться в отсутствии аллергической реакции.…”
Section: предупреждает развитие остеопорозаunclassified
“…La motivación para realizar la presente investigación se centra en la idea que un sistema médico experto es un programa informático que ayuda efectivamente en el diagnóstico y tratamiento siempre y cuando se aplique adecuadamente (11).…”
Section: Estado Del Arteunclassified
“…In Poland, an allergy to kiwi has not been subjected to epidemiological studies. In a study carried out by Bedoll-Pulido et al in Mexico, it was found that among 264 patients allergic to inhalant allergens, 6.6% had positive skin tests for kiwi, while only 2 (0.76%) displayed clinical symptoms [1]. To date, an exercise-related allergy to kiwi has not been reported.…”
Section: Introductionmentioning
confidence: 99%